A review of somaclonal variation in oil palm (Elaeis guineensis Jacq.) / Nur Aliyana Bahrum and Asmah Awal - Bahrum, Nur Aliyana; Awal, Asmah (Faculty of Plantation and Agrotechnology, 2018)
Cultivation of oil palm (Elates guineensis Jacq.) has expanded year by year with the main objective is to achieved high yield production. A research and development of tissue culture clonal propagation already start in the early 1970. The early success of plantlets production become inspiration for many oil palm organizations to explore in vitro propagation technique. With the present biotechnology, several micro propagation techniques such as callogenesis, organogenesis and somatic embryogenesis used for conventional breeding. Though oil palm tissue culture is already w-ell established, there is still many challenges to face for example is somaclonal variation. Somaclonal variation was first reported in 1986 which can be identify- by fruit mantling and abnormal vegetative growth which lead to obtained different result. In Malaysia, MPOB and AAR is the agencies that active in the development of oil palm propagation with many research and development have been conduct to produce high yielding clone. They able to prove that through better management, it can reduced mantling level to less than 5%. Hormone type, the length of culture period can become factors that contribute to the clonal abnormalities. This has been counter with the reducing hormone level and reducing culture period. The objective of this review are to identify- the factors and effect of somaclonal variation of oil palm and the methods on how- to overcome or to improve genetic variation. Through this review, several finding about Malaysian Standard for ortet selection (MS 2099:2008) that should be followed by all the oil palm tissue culture laboratories in Malaysia and several MPOB technologies in improving tissue culture have been find out.